Five‐year outcomes in kidney transplant patients randomized to everolimus with cyclosporine withdrawal or low‐exposure cyclosporine versus standard therapy. Issue 12 (3rd June 2018) - Sommerer, Claudia; Duerr, Michael; Witzke, Oliver; Lehner, Frank; Arns, Wolfgang; Kliem, Volker; Ackermann, Daniel; Guba, Markus; Jacobi, Johannes; Hauser, Ingeborg A.; Stahl, Rolf; Reinke, Petra; et al.
Abstract : HERAKLES was a 1‐year randomized, multicenter trial. Patients were randomized at 3 months after kidney transplantation to remain on cyclosporine‐based therapy, switch to everolimus without a calcineurin inhibitor (CNI), or switch to everolimus with low‐exposure cyclosporine. Overall, 417 of 497 (83.9%) patients from the core study entered a 4‐year extension study. The randomized regimen was continued to year 5 in 75.9%, 41.9% and 24.6% of patients in the standard‐CNI, CNI‐free and low‐CNI groups, respectively. Adjusted estimated GFR at year 5 was significantly higher in the CNI‐free group versus standard CNI (difference 7.2 mL/min/1.73 m 2, P < .001) or low CNI (difference 7.6 mL/min/1.73 m 2, P < .001). For patients who continued randomized therapy for 5 years, differences were 14.4 mL/min/1.73 m 2 and 10.1 mL/min/1.73 m 2, respectively. Biopsy‐proven acute rejection occurred during the 4‐year extension study in 7.6%, 8.6%, and 9.0% of patients in the standard‐CNI, CNI‐free and low‐CNI groups, respectively ( P = .927). In conclusion, conversion to a CNI‐free everolimus regimen 3 months after kidney transplantation improved long‐term graft function, particularly in patients who continued the CNI‐free regimen. Low CNI with everolimus did not improve renal function. Efficacy was comparable between groups but frequent immunosuppression changes should be taken into account. Abstract : Five‐year follow‐up data from patients randomized at three months after kidney transplantation to receive standard calcineurin inhibitor (CNI) therapy, everolimus‐based CNI‐free therapy, or everolimus with low‐exposure CNI show that early CNI withdrawal maintains better long‐term renal function without an increase in biopsy‐proven acute rejection, with a similar rate of infections and a low rate of discontinuations due to adverse events in all three treatment groups.